2009
DOI: 10.1242/jeb.027888
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the natural doping of migrant sandpipers in sedentary quails:effects of dietary n-3 fatty acids on muscle membranes and PPAR expression

Abstract: SUMMARYWild semipalmated sandpipers (Calidris pusilla) eat n-3 fatty acids to prime their muscles for long migrations. Sedentary bobwhite quails (Colinus virginianus) were used as a model to investigate the mechanisms for this natural doping. Our goal was to characterize the stimulating effects of n-3 eicosapentaenoic acid (EPA) and n-3 docosahexaenoic acid (DHA) on oxidative capacity. Mechanisms linked to changes in membrane composition and in gene expression for peroxisome proliferator-activated receptors (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 46 publications
(74 reference statements)
2
60
1
Order By: Relevance
“…43 Both fatty acids lead to an increased cellular membrane fluidity and serve as ligands for peroxisome proliferators-activated receptors, 44 which are involved in regulation of lipid metabolism. Different types of fatty acids, however, are not identical in their effects on performance 45 or health.…”
Section: Discussionmentioning
confidence: 99%
“…43 Both fatty acids lead to an increased cellular membrane fluidity and serve as ligands for peroxisome proliferators-activated receptors, 44 which are involved in regulation of lipid metabolism. Different types of fatty acids, however, are not identical in their effects on performance 45 or health.…”
Section: Discussionmentioning
confidence: 99%
“…Wintering and migratory western sandpipers showed strong positive correlations between plasma n-3 PUFA and pectoralis HOAD and CPT activities, but not CS activity or H-FABP protein content (Guglielmo, 2010). Further support for natural doping came from a dosing study of non-migratory bobwhite quail (Colinus virginianus), which responded to daily supplementation with oils high in 20:5n-3 (59%) and 22:6n-3 (70%) by increasing pectoralis activities of CS, CPT, HOAD and COX (Nagahuedi et al, 2009). However, it is not certain that the correlations measured in sandpipers represent cause and effect, or that the variation in muscle enzyme activities meaningfully affect flight performance.…”
Section: Potential Benefits Of Unsaturated Fatty Acids For Migrantsmentioning
confidence: 99%
“…The authors relate this change to the consumption of an amphipod, containing high amounts of n-3 polyunsaturated fatty acids. In later laboratory experiments it was shown that unsaturated dietary fatty acids could increase oxidative enzymes by up to 90% in sedentary quail muscles, whereby observed functional changes were attributed to changes in membrane fluidity and PPAR expression (Nagahuedi et al, 2009). Observations on migratory birds further indicate that flight muscle mass changes seasonally by up to 40% in red knots, Calidris canutus, kept in captivity, under constant photoperiod and without evidence of exercise training (Dietz et al, 1999;Pierce and McWilliams, 2014).…”
Section: Summary and Comparative Perspective Of Muscle Plasticitymentioning
confidence: 99%